Genetic determinants of apixaban plasma levels and their relationship to bleeding and thromboembolic events - Attelind, Sofia; Hallberg, Pär; Wadelius, Mia; Hamberg, Anna-Karin; Siegbahn, Agneta; Granger, Christopher B.; Lopes, Renato D.; Alexander, John H.; Wallentin, Lars; Eriksson, Niclas (Frontiers in Genetics, 2022)
Abstract Apixaban is a direct oral anticoagulant, a factor Xa inhibitor, used for the prevention of ischemic stroke in patients with atrial fibrillation. Despite using recommended dosing a few patients might still experience bleeding or lack of efficacy that might be related to inappropriate drug exposure. We conducted a genome-wide association study (GWAS) using data from 1,325 participants in the pivotal phase three trial of apixaban with the aim to identify genetic factors affecting the pharmacokinetics (PK) of apixaban. A candidate gene analysis was also performed for pre-specified variants in ABCB1, ABCG2, CYP3A4, CYP3A5 and SULT1A1, with a subsequent analysis of all available polymorphisms within the candidate genes. Significant findings were further evaluated to assess a potential association with clinical outcome such as bleeding or thromboembolic events. No variant was associated with an altered apixaban exposure on a genome-wide level. The candidate gene analyses showed a statistically significant association with a well-known variant in the drug transporter gene ABCG2 (c.421G>T, rs2231142). Patients carrying this variant had a higher exposure to apixaban (area under the curve [AUC], beta = 151 [95% CI 59 – 243], p = 0.001). On average, heterozygotes displayed a 5% increase of AUC and homozygotes a 17% increase of AUC, compared with homozygotes for the wild-type allele. Bleeding or thromboembolic events were not significantly associated with ABCG2 rs2231142. This large genome-wide study demonstrates that genetic variation in the drug transporter gene ABCG2 is associated with the pharmacokinetics of apixaban. However, the influence of this finding on drug exposure was small, and further studies are needed to better understand whether it is of relevance for ischemic and bleeding events.